Onemocnění asociované s imunoglobulinem IgG4. Klinické příznaky, diferenciální diagnostika a recentní mezinárodní diagnostická kritéria - Adam, Zdeněk; Zeman, David; Čermák, Aleš; Dastych, Milan; Doubková, Martina; Horváth, Theodor; Skorkovská, Šárka; Adamová, Zuzana; Řehák, Zdeněk; Koukalová, Renata; Pour, Luděk; Štork, Martin; et al. (Vnitrni lekarstvi, 2022)
Immunoglobulin G4- related disease (IgG4-RD) is a rare systemic fibro-inflammatory disorder. Autoimmune pancreatitis is the most frequent manifestation of IgG4-RD. However, IgG4-RD can affect any organ such as salivary glands, orbits, retroperitoneum, prostate and many others. Recent research enabled a clear clinical and histopathological description of IgG4-RD and in 2019 four Clinical phenotypes of IgG4-related disease were described. Diagnosis is based on morphological examination with typical findings of lymphoplasmocellular inflammation, storiform fibrosis and obliterative phlebitis in IgG4-RD biopsies and the tissue invading plasma cells largely produce IgG4. Elevated serum IgG4 levels are found in many but not all patients. New diagnostic criteria for IgG4-RD have been published recently in 2019 and 2021. This review summarizes current knowledge on pathophysiology, clinical manifestations, diagnosis and differential diagnosis of IgG4-RD from the point of view 2022 and in next article brings overview of the IgG4-RD therapy.
Keywords: autoimunitní nemoci; diferenciální diagnóza; Humans; Rare Diseases; imunoglobulin G; Immunoglobulin G4-Related Disease; Fibrosis; fibróza; IgG4 related disease; Inflammation; Diagnosis, Differential; lidé; IgG4 asociovaná nemoc; zánět; Autoimmune Diseases; Male; IgG4 immunoglobulin subclass; mužské pohlaví; Immunoglobulin G; vzácné nemoci